2012
DOI: 10.1111/j.1525-139x.2011.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance and Skill Retention after Simulation‐based Education for Nephrology Fellows

Abstract: We previously demonstrated that simulation-based education (SBE) improved temporary hemodialysis catheter (THDC) insertion skills by nephrology fellows. SBE, featuring deliberate practice and rigorous achievement standards, was a powerful method to enhance THDC insertion skills in nephrology fellows. However, experts have called for further research to evaluate skill transfer from the simulated environment to actual clinical care and skill retention. This is a prospective observational cohort study of THDC ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 22 publications
(28 reference statements)
3
86
1
Order By: Relevance
“…Because of the results of this study and others, we recommend rigorous simulation-based training for clinicians who insert THDCs. SBML results in improved THDC insertion skills that are retained over time, translates into the clinical environment (14), and is cost effective (24,27). We previously showed that this training can be provided for a large number of clinicians as part of an annual nephrology meeting (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the results of this study and others, we recommend rigorous simulation-based training for clinicians who insert THDCs. SBML results in improved THDC insertion skills that are retained over time, translates into the clinical environment (14), and is cost effective (24,27). We previously showed that this training can be provided for a large number of clinicians as part of an annual nephrology meeting (7).…”
Section: Discussionmentioning
confidence: 99%
“…Younger attending nephrologists may be more familiar with ultrasound use during IJ THDC insertion than older attending nephrologists, which may have led to improved checklist performance. It is also possible that THDC skills deteriorate over time when physicians are mostly supervising and not personally performing the procedure (14). Additional study is needed to determine the best mechanism to prepare attending nephrologists to perform and supervise THDC insertions in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were left with 30 (41%) articles after applying the exclusion and inclusion criteria. Six articles were related to student learning (3)(4)(5)(6)(7)(8), five were related to postgraduate trainees (9-13), and 19 were related to fellows or fellowship training (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). None of the articles had teachers or faculty members as subjects of the educational investigation.…”
Section: Literature Searchmentioning
confidence: 99%
“…Additional research in specialties, including nephrology, shows that, although initial training on simulators may show improved skills or capability in the learning, over time, there is a fairly significant decline, indicating that perhaps the strength of simulation is in ongoing training and practice, where all levels of learners return periodically to test and improve themselves (35). Okuda et al (36) summed it up nicely by concluding that most medical students, residents, and fellows will now do a fairly significant amount of training on simulators but relatively little data exist on the ultimate outcome of this work on patient outcomes.…”
Section: Simulation Center Simulation-based Learningmentioning
confidence: 99%